MURU'AH SEBAGAI KRITERIA 'ADALATU AL-RAWI - Sayid Muhammad Ramdhan (DIRAYAH : Jurnal Ilmu Hadis, 2022)
Experts in the science of hadith have laid down the rules and conditions of authentic hadith both in terms of matan and sanad. A narrator of authentic hadith must meet the criteria of al-'is (justice) which is built from several characteristics including the nature of muruah, namely a narrator is safe from things that damage his muruah (khawarim al-muruah). The scholars of hadith put a muruah limit in the justice of a narrator, but there are also those who do not make it a limit so that it does not injure the justice of the narrator and does not cause his history to be rejected. This study aims to analyze muruah as a criterion of justice for a narrator. This research uses qualitative method through literature study. The results and discussion of this study include the definition and examples of muruah, limitations and examples of khawarim al-muruah according to hadith experts, as well as an explanation of the terms muruah in 'is a narrator with examples. The conclusion of the study shows that muruah becomes the limit and condition of justice for a narrator but does not become the reason for the rejection of a history.